Mental and physical distress of field veterinarians during and soon after control of the 2010 foot and mouth disease outbreak in Miyazaki, Japan - Makita, K.; Tsuji, A.; Iki, Y.; Kurosawa, A.; Kadowaki, H.; Tsutsumi, A.; Nogami, T.; Watari, M. (2015)
An outbreak of foot and mouth disease occurred in Miyazaki, Japan in April 2010, and nearly 290,000 animals were culled to control the disease. This study was conducted to demonstrate the causes and intensity of mental distress encountered by the field veterinarians participating in the control programme. A focus group discussion was conducted with ten veterinarians to understand their distress during the outbreak, and a questionnaire to quantify the degree of distress experienced each week was administered to 16 veterinarians. A detailed questionnaire was separately administered to 70 veterinarians six months after the outbreak was controlled, to assess mental distress status and to identify the risk factors for serious mental illness (SMI) using the sixitem Kessler scale (K6). Overall, mental distress (mean 3.1) was significantly greater than physical distress (mean 1.9, p < 0.001). The risk factors for mental distress were categorised into three groups: culling, communication with farmers, and gender; each category was qualitatively described. Only two respondents (2.9%) had high K6 scores suggesting SMI. In the final generalised linear models with quasi-Poisson errors, the risk factors for SMI that remained were: disinfecting vehicles (p = 0.01), distress (p < 0.001), and increased alcohol consumption (p = 0.057), and a protective factor: participation in culling (p = 0.07), which suggested healthy worker bias. Sensitive individuals had been allocated to non-culling activities during disease control. In conclusion, human resource management was adequate during the outbreak from a public-health perspective. However, monitoring delayed symptoms of post-traumatic stress disorder is recommended.